Female narrative voices and old age as narrative objects in Argentine narrative: a comparative analysis (El Hilo de la Fabula, 2025)
This text will analyze the representations of elderly women as narratorial voices and objects of narrative in a corpus of texts belonging to contemporary Argentine narrative. One of the initial hypotheses is that female and elderly narratorial voices in contemporary Argentine literary works configure an alternative construction of the female identity and the experience of old age, challenging social and cultural stereotypes.The proposed objectives include, on the one hand, to analyze the characteristics of female and elderly narratorial voices in the works Más liviano que el aire, by Federico Jeanmaire (2009); Elena Sabe, by Claudia Piñeiro (2007) and Cae la noche tropical, by Manuel Puig (1988). On the other hand, to explore the relationships between memory, space and time present in the selected works regarding the construction of female identities and the experience of old age. Finally, to evaluate the way in which these representations challenge social and cultural stereotypes about old women and contribute to the construction of an alternative view of old age and the feminine.A textual, comparative and thematic analysis of the three literary works mentioned above will be carried out, using as theoretical references the notions of memory, space and time. Special attention will be paid to the narrative strategies used to construct the female and elderly narrator voices, as well as to the discourses and representations on old age and the feminine presented in the works.
Keywords: Elderly women; memory; space; time; Argentine narrative; Más liviano que el aire; Elena Sabe; Cae la noche tropical